2020 IEEE 20th International Working Conference on Source Code Analysis and Manipulation (SCAM) 2020
DOI: 10.1109/scam51674.2020.00010
|View full text |Cite
|
Sign up to set email alerts
|

Does code review really remove coding convention violations?

Abstract: Many software developers perceive technical debt as the biggest problems in their projects. They also perceive code reviews as the most important process to increase code quality. As inconsistent coding style is one source of technical debt, it is no surprise that coding convention violations can lead to patch rejection during code review. However, as most research has focused on developer's perception, it is not clear whether code reviews actually prevent the introduction of coding convention violations and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 28 publications
(46 reference statements)
0
2
0
Order By: Relevance
“…An investigation on the impact of code review on coding convention violation found that convention violations disappear after code reviews. However, only a minority of the violations were removed, because they were flagged in a review comment [119]. The comparison of cost required to produce quality programs using code reviews and pair programming showed that code reviews costs 28% less compared to pair programming [233].…”
Section: Impact Of Code Reviews On Product Quality and Human Aspects ...mentioning
confidence: 99%
“…An investigation on the impact of code review on coding convention violation found that convention violations disappear after code reviews. However, only a minority of the violations were removed, because they were flagged in a review comment [119]. The comparison of cost required to produce quality programs using code reviews and pair programming showed that code reviews costs 28% less compared to pair programming [233].…”
Section: Impact Of Code Reviews On Product Quality and Human Aspects ...mentioning
confidence: 99%
“…The first case study project's aim was to create a dataset of code reviews and the state of the software projects at the time of each code review to allow investigations about how code review impacts software projects. Not only was the dataset directly used in multiple projects (Paixão et al 2017(Paixão et al , 2019Han et al 2020;Paixão et al 2020), but it was created as a curated and reusable dataset that could be made publicly available (Paixão et al 2018). The case study serves as an example of ethics considerations when creating a dataset for public reuse.…”
Section: Case 1: Creation Of a Code Review Datasetmentioning
confidence: 99%